2015
DOI: 10.17770/etr2015vol3.174
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Attrition among First Year Computer Science Students: the Case of University of Latvia

Abstract: <p class="R-AbstractKeywords"><span lang="EN-GB">The purpose of our study was to identify reasons for high dropout of students enrolled in the first year of the computer science study program to make it possible to determine students, who are potentially in risk. Several factors that could affect attrition, as it was originally assumed, were studied: high school grades (admission score), compensative course in high school mathematics, intermediate grades for core courses, prior knowledge of program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…According to the conclusions of the primary study of the distribution of students [1], a majority of students really do not begin studies, therefore, activities targeting both "early" dropped out students and applicants are considered. Several ideas are planned to be studied further, for example, the possibility for students to assess themselves their suitability for a chosen field of study, by offering a variety of self-assessment tests -personality tests, logic tests, mathematics tests.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…According to the conclusions of the primary study of the distribution of students [1], a majority of students really do not begin studies, therefore, activities targeting both "early" dropped out students and applicants are considered. Several ideas are planned to be studied further, for example, the possibility for students to assess themselves their suitability for a chosen field of study, by offering a variety of self-assessment tests -personality tests, logic tests, mathematics tests.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, analysing students by the mathematics knowledge aptitude indicator, it is more important to analyse further exactly the weakest, less suitable, group of students, to plan further support activities. However, as a study of dropout showed [1], there is also a high dropout rate among students with more than 700 points, which is why the pre-enrolment activities aimed at prevention of dropout due to other reasons, including the wrong choice, are recommended to be conducted among this group of students as well.…”
Section: Current Situation With the Compensative Coursementioning
confidence: 99%
See 3 more Smart Citations